Sesame: A viable economic alternative for off-season double cropping systems in Mato Grosso, Brazil - Christo, Bruno Fardim; Lorenzoni, Rodrigo Monte; Marques Junior, Edilson; Nóia Júnior, Rogerio de Souza; Pagotto, Luís Otávio (Agrometeoros, 2024)
This study investigates the economic feasibility of sesame (Sesamum indicum L) cultivation as an alternative to off-season double cropping systems in Mato Grosso, Brazil, focusing on the period from 2016 to 2023. By employing a combination of qualitative and quantitative methodologies, it scrutinizes production costs, profitability, and climatic risks associated with both crops. The findings reveal that sesame cultivation entails consistently lower production costs, yielding superior margins, and exhibiting remarkable resilience against economic and climatic adversities compared to off-season maize. Despite minor fluctuations, sesame demonstrates stability in profitability, mitigating the impact of climatic risks on farmers' financial outcomes. This underscores sesame's potential to enhance farmers' financial resilience and bolster Brazil's position in global agricultural markets amidst climatic uncertainties. Furthermore, the study highlights sesame's role in promoting sustainable agricultural practices and enhancing food security. Through its comprehensive analysis, this research not only underscores the economic advantages of sesame cultivation but also emphasizes the importance of considering climatic risks in agricultural decision-making. By offering invaluable insights into the economic viability of sesame cultivation amidst climatic challenges, this study contributes to informed policy formulation and agricultural practice refinement in Brazil.